Structural performance and design of stainless steel gusset plate connections - Khine Myint Myat Thein (Nanyang Technological University, 2022)
A numerical study on stainless steel open sections connected to gusset plate has been conducted and presented in this report. An experimental study using 16 test specimens for angle-to-gusset plate connection and 16 specimens for channel-to-gusset plate were observed as a benchmark for this research.